If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 15) = (3x + -5) Reorder the terms: (15 + 2x) = (3x + -5) Remove parenthesis around (15 + 2x) 15 + 2x = (3x + -5) Reorder the terms: 15 + 2x = (-5 + 3x) Remove parenthesis around (-5 + 3x) 15 + 2x = -5 + 3x Solving 15 + 2x = -5 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 15 + 2x + -3x = -5 + 3x + -3x Combine like terms: 2x + -3x = -1x 15 + -1x = -5 + 3x + -3x Combine like terms: 3x + -3x = 0 15 + -1x = -5 + 0 15 + -1x = -5 Add '-15' to each side of the equation. 15 + -15 + -1x = -5 + -15 Combine like terms: 15 + -15 = 0 0 + -1x = -5 + -15 -1x = -5 + -15 Combine like terms: -5 + -15 = -20 -1x = -20 Divide each side by '-1'. x = 20 Simplifying x = 20
| 2tan(3x)=7 | | F(x)=4x^2-16 | | 2(x-2)=52-5x | | 103=x^2+5 | | 3(2x-3)+3(x-2)+2(2x+1)=5(x-1) | | 4x+18=35+5x | | (4x+1)=(6x-5) | | 2r^2=6r+20 | | 4x^5-20x^4-36x^3= | | 120-12(3-4(2*3-2*(-8)))= | | 5y/8-2=7y/12 | | 5(6y-5)=11(3y-2) | | F=5e-3 | | 0,36x-2,3=0,5(0,4x+1,2) | | 3x+17x-4=5(4x+2) | | g^2-28g+196= | | 3k^2=16 | | 9x+6x-5=15x+3 | | 4x-2=360 | | 3.7=-log(x) | | -26=-3t^2+28 | | -26=-3t+8 | | 2*ln(x)-ln(5)=ln(2) | | 3xy(z-5)+4m(5-z)=0 | | x-2(18/4)=3 | | 7y^2(x-5)-5(x-5)=0 | | -2a^2+19=-21 | | 3x+4=3(x+1)+1 | | T(n)=4n+2 | | 2x-xsquared+16=0 | | 3x+4=3(x+1) | | -2a+19=-21 |